Interprofesional Education Tentang Flour Albus Dan Perawatan Higiene Vaginal Dengan Kejadian Flour Albus Pada Remaja Putri Di Sekolah Menengah Atas Wilayah Kabupaten Sukabumi - Situmorang, Roganda; Anri; Situmorang, Elisa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Vaginal discharge in adolescent girls is an asset of future reproductive health that has the potential for infection and death. Sukabumi Health Office seeks to improve reproductive health, especially in adolescents and identified one of the schools in Sukabumi Regency as having reproductive health problems regarding vaginal discharge and hygiene of the feminine area. To determine the relationship between knowledge about vaginal discharge and vaginal hygiene behavior with the incidence of flour albus in adolescent girls in Senior High Schools in Sukabumi Regency. Methods: Quantitative research method, descriptive correlation type, cross sectional approach. The population is all adolescent girls in one of the Senior High Schools in Sukabumi Regency totaling 109 people, the sample is determined by the Lameshaw formula of 52 adolescent girls selected by random sampling. Data were taken using a questionnaire and using univariate frequency distribution calculation analysis and chi-square bivariate analysis Results: The results showed that almost half (28.8%) of adolescent girls had poor knowledge of vaginal discharge, almost half (38.5%) of adolescent girls had poor vaginal hygiene behavior and most (57.7%) of adolescent girls experienced vaginal discharge. There is a relationship between knowledge about vaginal discharge (p-value 0.038) and vaginal hygiene behavior (p-value 0.010) with the incidence of flour albus in female high school adolescents in Sukabumi Regency. Conclusion: There is a significant relationship between knowledge about vaginal discharge and vaginal hygiene behavior with the incidence of flour albus in female adolescents and it is recommended to increase the strengthening of digital-based education by health centers by nurses and midwives about flour albus health education and vaginal hygiene behavior training programs